Antimicrobial resistance profile of planktonic and biofilm cells of staphylococcus aureus and coagulase-negative staphylococci - de Oliveira, Adilson [UNESP]; Pereira, Valéria Cataneli [UNESP]; Pinheiro, Luiza [UNESP]; Riboli, Danilo Flávio Moraes [UNESP]; Martins, Katheryne Benini [UNESP]; de Lourdes Ribeiro de Souza da Cunha, Maria [UNESP] (MDPI, 2016)
The objective of the present study was to determine the antimicrobial resistance profile of planktonic and biofilm cells of Staphylococcus aureus and coagulase-negative staphylococci (CoNS). Two hundred Staphylococcus spp. strains were studied, including 50 S. aureus and 150 CoNS strains (50 S. epidermidis, 20 S. haemolyticus, 20 S. warneri, 20 S. hominis, 20 S. lugdunensis, and 20 S. saprophyticus). Biofilm formation was investigated by adherence to polystyrene plates. Positive strains were submitted to the broth microdilution method to determine the minimum inhibitory concentration (MIC) for planktonic and biofilm cells and the minimal bactericidal concentration for biofilm cells (MBCB). Forty-nine Staphylococcus spp. strains (14 S. aureus, 13 S. epidermidis, 13 S. saprophyticus, 3 S. haemolyticus, 1 S. hominis, 3 S. warneri, and 2 S. lugdunensis) were biofilm producers. These isolates were evaluated regarding their resistance profile. Determination of planktonic cell MIC identified three (21.4%) S. aureus strains that were resistant to oxacillin and six (42.8%) that were resistant to erythromycin. Among the CoNS, 31 (88.6%) strains were resistant to oxacillin, 14 (40%) to erythromycin, 18 (51.4%) to gentamicin, and 8 (22.8%) to sulfamethoxazole/trimethoprim. None of the planktonic isolates were resistant to vancomycin or linezolid. MICs were 2-, 4-, 8-, and up to 16-fold higher for biofilm cells than for planktonic cells. This observation was more common for vancomycin and erythromycin. The MBCB ranged from 8 to >256 μg/mL for oxacillin, 128 to >128 μg/mL for vancomycin, 256 to >256 μg/mL for erythromycin and gentamicin, >64 μg/mL for linezolid, and 32/608 to >32/608 μg/mL for sulfamethoxazole/trimethoprim. The results showed considerably higher MICs for S. aureus and CoNS biofilm cells compared to planktonic cells. Analysis of MBCM confirmed that even high concentrations of vancomycin were unable to eliminate the biofilms of S. aureus and CoNS species. Linezolid was the most effective drug in inhibiting staphylococci in the biofilm, without an increase in the MIC, when compared to planktonic cells. None of the isolates were resistant to this drug.
Keywords: Antimicrobials; Biofilm; Coagulase-negative staphylococci; Resistance; Staphylococcus aureus